2004
DOI: 10.1037/0002-9432.74.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Psychological Reactions 7 Weeks After the 1995 Oklahoma City Bombing.

Abstract: This study assessed teachers' reactions to the Oklahoma City bombing. Peritraumatic reactions, the interaction of media exposure with stress from media coverage, feelings toward the perpetrators, and worry about safety predicted posttraumatic stress. Twenty percent reported difficulty handling demands; 5% sought counseling. Outreach efforts should assess and assist teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
2
11
1
Order By: Relevance
“…Although levels of secondary trauma related to school shooting were somewhat low and positively skewed, both ATTs and ISSM positively and significantly correlated with teachers’ reported secondary trauma. Similar to the results of Heir et al (), Silver et al (), and Pfefferbaum et al (), a small, but concerning percentage (16%) of teachers indicated levels of secondary trauma that would warrant concern (i.e., an average of indicating they “occasionally” experienced the listed symptoms). However, unlike the research of secondary trauma following large‐scale traumatic events related to terrorist attacks and natural disasters, which fortunately occur infrequently, the study of secondary trauma related to school shootings is an investigation of events which occur multiple times throughout the year.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although levels of secondary trauma related to school shooting were somewhat low and positively skewed, both ATTs and ISSM positively and significantly correlated with teachers’ reported secondary trauma. Similar to the results of Heir et al (), Silver et al (), and Pfefferbaum et al (), a small, but concerning percentage (16%) of teachers indicated levels of secondary trauma that would warrant concern (i.e., an average of indicating they “occasionally” experienced the listed symptoms). However, unlike the research of secondary trauma following large‐scale traumatic events related to terrorist attacks and natural disasters, which fortunately occur infrequently, the study of secondary trauma related to school shootings is an investigation of events which occur multiple times throughout the year.…”
Section: Discussionsupporting
confidence: 79%
“…Pfefferbaum et al () found subsequent television exposure related to the 1995 Oklahoma City bombing of the Alfred P. Murrah Federal Building to be a statistically significant predictor of posttraumatic stress in Oklahoma City teachers who resided within six miles of the terrorist attack. Although the effect size was small, the researchers only asked two questions related to television viewing.…”
Section: Introductionmentioning
confidence: 99%
“…The few prior studies examining teacher response to crises have tended to focus generally on trauma, rather than on a specific crisis event (Alisic, 2012), have collected data after considerable time has passed (Felix et al, 2010), or focused on the psychological reactions of teachers, rather than on their perceptions of and response to students (Pfefferbaum et al, 2004). Several key findings emerge from the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Safety is associated not only with the absence of intentional or unintentional harm but also with a perception that one is being protected or sheltered from harm. Research on safety is linked to events such as the Chernobyl disaster of 1986, the Oklahoma bombing of 1995, and the terrorist attacks of 2001 (Maurice et al, 2001;Pfefferbaum et al, 2004;Schuster et al, 2001). Lower perception of safety was associated with greater symptoms of intrusion and hyperarousal in disaster workers after 9=11 (Fullerton, Ursano, Reeves, Shigemura, & Grieger, 2006).…”
Section: Sense Of Safety and Anxietymentioning
confidence: 96%